2019
DOI: 10.1016/j.lwt.2018.10.055
|View full text |Cite
|
Sign up to set email alerts
|

A starch edible surface coating delays banana fruit ripening

Abstract: A rice starch edible coating blended with sucrose esters was developed for controlling the postharvest physiological activity of Cavendish banana to extend postharvest quality during ripening at ± 2°C. Coating effectiveness was assessed against changes in fruit physiochemical parameters such as weight loss, titratable acidity, total soluble solids, flesh fruit firmness, ion leakage, colour change, respiration, ethylene production, chlorophyll degradation and starch conversion were determined. The topography of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
66
1
6

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 152 publications
(80 citation statements)
references
References 29 publications
7
66
1
6
Order By: Relevance
“…Whereas, Chakkarakeli (AAB group) banana fruits firmness analysis shown that T1, T2, T3 coatings have also increase in 1.97‐, 2.4‐, 2.77‐fold to control fruits, respectively. The similar results were also reported in Cavendish banana using starch blended coatings (Thakur et al, ). Softening of fruits is related to a change in cell wall component and starch degradation (Perera et al, ).…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…Whereas, Chakkarakeli (AAB group) banana fruits firmness analysis shown that T1, T2, T3 coatings have also increase in 1.97‐, 2.4‐, 2.77‐fold to control fruits, respectively. The similar results were also reported in Cavendish banana using starch blended coatings (Thakur et al, ). Softening of fruits is related to a change in cell wall component and starch degradation (Perera et al, ).…”
Section: Resultssupporting
confidence: 88%
“…The similar results were also reported in Cavendish banana using starch blended coatings (Thakur et al, 2019). Softening of fruits is…”
Section: Physical Parameters Analysissupporting
confidence: 86%
See 3 more Smart Citations